An international consensus statement on the management of postoperative anaemia after major surgical procedures. (31st July 2018) - Muñoz, M.; Acheson, A. G.; Bisbe, E.; Butcher, A.; Gómez‐Ramírez, S.; Khalafallah, A. A.; Kehlet, H.; Kietaibl, S.; Liumbruno, G. M.; Meybohm, P.; Rao Baikady, R.; Shander, A.; et al.
Summary: Despite numerous guidelines on the management of anaemia in surgical patients, there is no pragmatic guidance for the diagnosis and management of anaemia and iron deficiency in the postoperative period. A number of experienced researchers and clinicians took part in a two‐day expert workshop and developed the following consensus statement. After presentation of our own research data and local policies and procedures, appropriate relevant literature was reviewed and discussed. We developed a series of best‐practice and evidence‐based statements to advise on patient care with respect to anaemia and iron deficiency in the postoperative period. These statements include: a diagnostic approach to iron deficiency and anaemia in surgical patients; identification of patients appropriate for treatment; and advice on practical management and follow‐up that is easy to implement. Available data allow the fulfilment of the requirements of Pillar 1 of Patient Blood Management. We urge national and international research funding bodies to take note of these recommendations, particularly in terms of funding large‐scale prospective, randomised clinical trials that can most effectively address the important clinical questions and this clearly unmet medical need. Abstract : 手術患者の貧血管理に関するガイドラインは多数あるものの, その中で術後の貧血および鉄欠乏の診断と管 理に関する実用的な治療指針は示されていない。本稿では, 多数の経験豊富な研究者および臨床医が参加し た2 日間の専門ワークショップで作成された合意声明文について報告する。このワークショップでは, 著者ら自身の研究データと各国の方針および手順が発表され, 続いて適切な関連文献のレビューとそれに関する議 論が行われた。エビデンスに基づいた最善の治療に関する, 術後の貧血と鉄欠乏に関わる患者のケアについ ての一連の声明が作成された。この声明では, 手術患者の鉄欠乏と貧血を診断する方法, 治療の適応となる 患者の特定, 実践しやすい実際の管理とフォローアップに関する意見が示されている。これまでに得られたデータは「患者中心の輸血管理法(Patient Blood Management)」の最初の論拠となるにすぎない。重要なクリニカルクエスチョンと, まだ満たされていないメディカルニーズに対して, 最も効率的に言及できるよ うな大規模前向き無作為化臨床試験への資金提供という観点から, 国内外の研究資金支援団体が本推奨事項 に注目することを期待する。